All Days 2010
DOI: 10.2118/140680-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Artificial Neural Network Approaches to Predict the Effect of PVA (Poly Vinyl Acetate) on the Rheological Properties of Water and Crude Oil in EOR Processes

Abstract: As consequence of pressure drop in oil reservoirs, production of oil will be difficult and EOR methods are used to improve recovery. In many countries Polyacrylamide is used for polymer flooding in EOR processes, but the problem is that Polyacrylamide is expensive also Acrylamide needs to be handled using best laboratory practices (such as having safe systems of work and wearing appropriate gloves, lab coat etc.) to avoid poisonous exposure since it is a neurotoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The decrease in mobility of water can have an effect on oil recovery. It was also reported that the addition of PVA into crude oil resulted in viscosity reduction …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The decrease in mobility of water can have an effect on oil recovery. It was also reported that the addition of PVA into crude oil resulted in viscosity reduction …”
Section: Introductionmentioning
confidence: 94%
“…Thus, to fully hydrolyze PVA (i.e., hydrolyze ≥ 98%), elevated temperatures greater than 353.15 K will be required . Not much information regarding the application of PVA at elevated temperatures is available in the literature . However, some works in other fields have been reported on the rheological properties of PVA. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the promising applications of artificial intelligence and genetic programming in estimating important parameters for reservoir engineering and process improvement, these methods can also be applied to estimate and optimize polymer flooding processes in enhanced oil recovery, through estimating values of viscosity of polymeric solutions and the prediction of the performance of these injection fluids in reservoirs. In this context, several authors have developed researches focused on this area (Rezaian et al, 2010;Kang et al, 2016;Amirian et al, 2018;Corredor-Rojas et al, 2018;Rostami et al, 2018b). Rezaian et al (2010) applied the artificial neural network model to estimate the minimum amount of Polyvinyl Acetate (PVA) needed to increase water viscosity and simultaneously promote a decrease in oil viscosity, and thus improve the polymer flooding process.…”
Section: Artificial Intelligence Applicationmentioning
confidence: 99%
“…In this context, several authors have developed researches focused on this area (Rezaian et al, 2010;Kang et al, 2016;Amirian et al, 2018;Corredor-Rojas et al, 2018;Rostami et al, 2018b). Rezaian et al (2010) applied the artificial neural network model to estimate the minimum amount of Polyvinyl Acetate (PVA) needed to increase water viscosity and simultaneously promote a decrease in oil viscosity, and thus improve the polymer flooding process. To test the effectiveness of the created network, experimental tests were carried out and these showed agreement between the estimated percentages and those obtained in the experiment.…”
Section: Artificial Intelligence Applicationmentioning
confidence: 99%